Teaching assistants' competencies and the community of inquiry at an open distance learning institution - Setlhako, Motladi Angeline (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper reports on qualitative research conducted in one department at an Open Distance Learning Institution. The participants were 21 e-tutors/teaching assistants (TAs) who facilitated an online compulsory module for certificate and degree seeking students in Education called “Being a Professional Teacher (BPT)”. It is a bridging course aimed at students who wish to register for a degree in education for the first time. The TAs who facilitated the BPT programme had tacit assumptions about the pedagogy (classroom based) they would use in the online environment. To help both the TAs and their trainer, the researcher conducted this initial research with a focus on the skills/competencies needed by the TAs. Through the lens of competencies, it was possible to place the study within a larger inquiry into the question about their teaching practices in an online environment. Adaptation, modification and deconstruction of teaching practices require change, which takes time and reflection. In low context communication environments, such as an e-learning environment, that change is expected to be rapid. The rapidity of change is dependent on socio-cognitive and socio-affective development of the persons who must change. The TAs did adapt quite rapidly. The three presences needed for a Community of Inquiry to be successful, namely teaching, social and cognitive presences were indicated as developing through a discussion of the competencies the TAs started with, developed during the teaching of BPT and what they still needed to acquire in the future.